Development of an electrochemical microsensor for monitoring the respiration activity of single cells and animals by scanning electrochemical microscopy - Santos, Carla Santana (2019)
This thesis shows results on the development of an O2 micro/nanosensor for scanning electrochemical microscopy (SECM) application with the aim of monitoring changes in respiration activity over a single cell. The surface of platinum microelectrodes was modified by using a platinisation protocol in order to facilitate the eletron-transfer process regarding the O2 reduction reaction, hence the sensitivity of the device was greatly enhanced. The stability of the microsensor and the nature of oxygen reduction reaction (ORR) products were also evaluated by SECM. The developed microsensor was employed in redox competition SECM operating mode to monitor local changes in the O2 concentration of a single-cell (HS578T lineage) present in phosphate buffer medium during the addition of specific compounds to modulate the mitochondria activity. A similar protocol was used for examining the metabolism of a nematode (Caenorhabditis elegans) by scanning the O2 microsensor over a single-animal, with particular attention being devoted to the reproductive system. Hence, SECM has been proven to be a powerful and reliable technique to investigate biochemical events related to cellular activity by means of oxygen consumption rate (OCR) with high spatial resolution. The last section of this thesis presents a novel scanning probe microscopy developed in the Prof. Schuhmanns group (Germany) employing bipolar electrochemistry concepts. The scanning bipolar electrochemical microscopy (SBECM) allows the independent acquisition of multi-microelectrodes responses localized close to a surface. In contrast of scanning a single probe as the conventional SECM, higher temporal resolution is obtained with SBECM. The results showed in this thesis confirmed the ability of the electrochemical probe techniques to acquire local O2 concentration information and to provide deeper insight and comprehensive aspects in the biological area.